Rancang Bangun Alat Pembaca Uji Kompresi Beton Dan Mortar Otomatis Berbasis Arduino - Jatnika; Mukhlis Ali (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2022)
In the construction process, the calculation of the strength of concrete and mortar is very important to avoid realko from accidents in buildings that fail. Concrete and mortar structures with good quality are still being tested for strength so that they are sexual with predetermined national standards. Concrete and mortar are elements in construction which are simple structures formed by a mixture of cement, water, fine aggregate, coarse aggregate consisting of crushed stone or gravel, and other mixed materials. Concrete is usually applied to foundations, columns, slab beams, culverts, weirs and dams. The creation of a concrete compressive strength test tool with an automation system based on a microcontroller, the design of an effective and simple concrete compressive strength machine control device, can test the hardness level of a concrete test object. both in accordance with applicable SNI in civil engineering. For Testing the Compressive Strength of concrete is the maximum force per unit area acting on concrete specimens. Concrete compressive strength testing is carried out based on SNI 03-6882. The Arduino Uno microcontroller-based concrete compressive strength test tool is specifically designed for concrete and mortar testing. not too complicated and the operation does not require special skills and components can be easily found in the market so that the manufacture and replacement of spare parts can be done easily.